Characteristics Of Organic Coffee Consumers - Hariyanto, Adi; Noer, Irmayani; Kurniawan, Henry; Analianasari, Analianasari (Journal of International Conference Proceedings, 2025)
Nowadays, people are starting to realize the importance of health and environmental sustainability. Organic coffee is one of the alternatives chosen to support lifestyle and maintain environmental sustainability for consumers and coffee lovers. This study aims to describe the characteristics of respondents who consume organic coffee. The analysis method used in this study is the descriptive analysis method. The sampling method in this study is the accidental sampling technique of 100 respondents. The results of the study show that the majority of organic coffee consumers are men, namely 54% with ages 21-33 years with a percentage of 87% with an unmarried status of 68% with the majority of S1/S2/S3 education of 63% and work as private employees of 41% with an income of Rp 6,000,000 - Rp 9,000,000 of 37%. The primary motivation for consumption is health reasons (78%), followed by environmental concerns (19%). Social media is the primary source of information (53%), and online stores are the most common purchasing channel (52%). These findings indicate that the organic coffee market has significant growth potential, especially through targeted value-based marketing and digital education approaches.